Getting Healthy by Catching Them All: A Study on the Relationship Between Player Orientations and Perceived Health Benefits in an Augmented Reality Game - Koivisto Jonna; Malik Aqdas; Gurkan Bahadir; Hamari Juho (United States, 2022)
In recent years, location-based augmented reality games such as Pokémon Go have become increasingly popular. These games not only afford a novel gaming experience, but also have the potential to alter how players view their physical realities and alter the dynamics of traditional game play from its sedentary nature towards a more physical one. In this paper we investigate what kinds of players (achievement, immersion or social interaction -oriented) are more likely to derive health benefits from playing augmented reality games. We employ online survey data gathered among players of Pokémon Go (N=1190). The results show that playing location-based augmented reality games has a positive association with perceived mental, physical and social health outcomes overall. The results also suggest that the way in which players approach the game and what kinds of aspects of the game they emphasize can have a differential dynamic on how the health benefits of the game manifest. Results show that social gaming orientation is positively associated with physical, mental and social health outcomes, whereas achievement and immersion orientations are associated with physical and mental health outcomes.
Proceedings of the 52nd International Conference on System Sciences